2005
DOI: 10.1104/pp.104.051045
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Aquaporins and Membrane Damage in Chilling and Hydrogen Peroxide Induced Changes in the Hydraulic Conductance of Maize Roots  

Abstract: When chilling-sensitive plants are chilled, root hydraulic conductance (L o ) declines precipitously; L o also declines in chillingtolerant plants, but it subsequently recovers, whereas in chilling-sensitive plants it does not. As a result, the chilling-sensitive plants dry out and may die. Using a chilling-sensitive and a chilling-tolerant maize genotype we investigated the effect of chilling on L o , and its relationship to osmotic water permeability of isolated root cortex protoplasts, aquaporin gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
190
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 231 publications
(210 citation statements)
references
References 64 publications
16
190
0
Order By: Relevance
“…At the mRNA level, decreased expression of individual PIP genes during chilling was observed in rice [19,7], maize [6] and Arabidopsis [20]. We determined the expression of all the 11 PIP genes by real-time RT-PCR using TaqMan-MGB probes, and found that chilling reduced the expression of most PIP genes in our experiments (Figure 3), a result consistent with a previous report [7].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…At the mRNA level, decreased expression of individual PIP genes during chilling was observed in rice [19,7], maize [6] and Arabidopsis [20]. We determined the expression of all the 11 PIP genes by real-time RT-PCR using TaqMan-MGB probes, and found that chilling reduced the expression of most PIP genes in our experiments (Figure 3), a result consistent with a previous report [7].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, chilling led to a dramatic decrease in osmotic root Lp in Somewake and Wasetoitsu ( Figure 2C), an observation that paralleled observations in maize [3,6], spinach [9], bean [8], cucumber and figleaf gourd [12]. The water imbalance was probably triggered by the sharp drop in root water uptake at the onset of chilling, whereas decreased transpiration occurred later ( Figure 2B).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations